The Discourse of Meaning of Jihad in Muhammadiyah Circle (A Hermeneutics Perspective) - Romadlan, Said (Komunikator, 2019)
This study focuses on the discourse about the meaning of Jihad that emerged in the Muhammadiyah circle as one of the Islamic Organizations in Indonesia. The discussion of meaning of Jihad as a way of peace or a way of war becomes crucial amid radicalism, terrorism, violence movements and chaos waged on behalf of religion. However, Muhammadiyah believes that the meaning of Jihad is anti-war and anti-violence which strengthens the understanding of Islam as the religion of rahmatan lil alamin (a mercy to all creation). This belief is criticism and contra-discourse towards camps that perceive Jihad as war and acts of violence. This study uses Paul Ricoeur's Interpretation Theory and focuses on the interpretation of the text based on the distinction between the text and the reader. The method is Ricoeur's hermeneutic method which focuses on the distortion of language, discourse, and textuality. The study shows that textually the meaning of Jihad among the Muhammadiyah circle is jihad lil-muwajahah, or the struggle to tackle a challenge by creating a superior movement, for example, ?Jihad Konstitusi.? Muhammadiyah's understanding of the meaning of Jihad can be used as a counter-discourse on the meaning of Jihad which well known as an act of terrorism.